Formação Sindical e Coesão Institucional na CUT - Silva, Vagner Luís da (2007)
In view of the growing centrality that the educational area holds in the today’s world, it’s important to explore the several moments it presents. Thus, the article tries to underline a theme not always remembered in the subject research: the unionist formation as institutional instrument of unity. The central concerning, here, is to explore the limits of CUT institutional cohesion with a sample of its membership base. The empiric focus falls upon the unionist formation. More properly in the way CUT, using of its formations project, tries to spread a behavior standard and, as a consequence, as the unions absorb such standard.